2018
DOI: 10.1136/bmjopen-2017-019787
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the facility-based maternal near-miss case reviews in improving maternal and newborn quality of care in low-income and middle-income countries: a systematic review

Abstract: ObjectivesThe maternal near-miss case review (NMCR) has been promoted by WHO as an approach to improve quality of care (QoC) at facility level. This systematic review synthesises evidence on the effectiveness of the NMCR on QoC and maternal and perinatal health outcomes in low-income and middle-income countries (LMICs).MethodsStudies were searched for in six electronic databases (MEDLINE, Index Medicus, Web of Science, the Cochrane library, Embase, LILACS), with no language restrictions. Two authors independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Interviewing mothers has been a WHO recommendation for the review of maternal near-miss cases for a long time and has shown a significant effect in reducing maternal mortality. 43 Currently, WHO, in agreement with several other agencies and bodies, recommends to routinely explore several aspects of women’s ‘experience of care’ in order to identify actions to improve the quality of maternal and newborn care at the facility level. 6 7 …”
Section: Discussionmentioning
confidence: 99%
“…Interviewing mothers has been a WHO recommendation for the review of maternal near-miss cases for a long time and has shown a significant effect in reducing maternal mortality. 43 Currently, WHO, in agreement with several other agencies and bodies, recommends to routinely explore several aspects of women’s ‘experience of care’ in order to identify actions to improve the quality of maternal and newborn care at the facility level. 6 7 …”
Section: Discussionmentioning
confidence: 99%
“…Establishment of a maternal and perinatal database across selected referral hospitals for routine collection of data during labour, childbirth, and the postpartum period (as planned by WHO in collaboration with the Nigerian Ministry of Health) would facilitate such quality improvement strategy. There is evidence to suggest that implementing near‐miss case reviews can improve the quality of maternity care and/or reduce maternal morbidity and mortality in low‐ and middle‐income country hospitals . Implementation of a near‐miss case review system should consider not only the data requirements (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The study of women who survived a life-threatening complication enables the identification of the shortcomings and successes regarding assistance, and it also enables physicians to deepen the understanding of the disease process from the perspective of the patients, situations that are not possible in cases of maternal death. [7][8][9] Since the last decade, several studies have been using bibliometric methods to evaluate scientific productivity in several biomedical fields. 8,9 Although the measurement of the rate of MNM is promoted as an indicator of the quality of maternal health care, 6,10 in the scientific literature there is a lack of studies that estimate the global production of research on MNM.…”
Section: Introductionmentioning
confidence: 99%